Solubilidade da arginina, do glutamato de sódio e do ibuprofeno em soluções organo-aquosas - Silva, Taciana Barros e (2025)
The study of solubility is extremely relevant for drug production and absorption, as well as for the purification of products through crystallization, and for understanding solid-liquid equilibrium. In this work, the solubility of arginine, monosodium glutamate, and ibuprofen in the water-ethanol and water-propylene glycol solvent systems was experimentally determined through the isothermal method and analyzed at temperatures ranging from 25 to 50°C. The solids in equilibrium were characterized by X-ray diffraction (XRD) and optical microscopy (OM). The solubility results obtained were used to fit thermodynamic models: for arginine and monosodium glutamate, only Apelblat and λh models were used, while for ibuprofen, the Apelblat, λh and Wilson models were applied. For all compounds and solvent systems, solubility increased with temperature. The experimental solubility data for arginine and ibuprofen showed behavior similar to that reported in the literature. For sodium glutamate, no previous studies on its solubility were found, to the best of our knowledge. Among all the studied conditions and within the analyzed temperature range, the Apelblat model provided the best fits. According to the Wilson model, at certain temperatures, all components in the system influence molecular interactions, and as the temperature rises above 35 °C, the model becomes less accurate in representing the solubility of ibuprofen. For all three compounds, the solubilization process is endothermic, favored by entropy, although limited by endothermicity, non-spontaneous, as the values of ΔH, ΔS, and ΔG were positive, except for sodium glutamate in pure water, where ΔS was negative, and driven by enthalpy. X-ray diffraction showed that, for both arginine and glutamate, there are two possible different forms in equilibrium in the systems. For arginine, optical microscopy indicated similar crystal habits between the water-ethanol 15%, water-ethanol 30%, and water-propylene glycol 15% systems, and a similarity between the water-propylene glycol 30% system and pure water. This differs from the XRD results and may be explained by a possible recrystallization. For monosodium glutamate, the crystals in all systems showed similar crystal habits. For ibuprofen, the XRD revealed that none of the studied systems closely resembled the enantiomer (S)-ibuprofen or (R)-ibuprofen, nor the (R,S)-ibuprofen, suggesting the possible presence of mixtures with varying proportions of (S)- and (R,S)-ibuprofen. However, optical microscopy indicated similar crystal habits between the crystals of the water-ethanol system for all compositions and pure propylene glycol.